The Relation between Worker Protection System in the Interpersonal Service and Workplace Violence as Well as Workers' Depression - Eun-Hi Choi; Myung-Hee Jung; Eun-Mi Beak; Hye-Sun Jung; Bokim Lee (Tehran University of Medical Sciences, 2022)
Background: We aimed to confirm the effect of interpersonal service worker protection system on workplace violence and depression and to determine the relationship among the protection system, workplace violence, and depression. Methods: Self-reporting survey was conducted for approximately a month beginning on 2 March 2020, among members selected using the convenience sampling method from seven labor unions in South Korea to which interpersonal service workers belonged. The questionnaire consisted of questions regarding the subjects' general characteristics, worker protection system, workplace violence, and depression. Overall, 1,541 workers participated in this study. Results: The basic model was used to test the relationship between the protection system and depression, with a mediating effect of workplace violence. Three of the hypothesized paths were significant (P<.001), but the basic model did not fit the data. In the revised model, the direct path from the protection system to depression was deleted. Path coefficient of the direct effect of the protection system on violence was -0.05, the direct effect of the violence on depression was 0.77, and the indirect effect of the protection system on depression was -0.04. The fit of this model was acceptable. Conclusion: Organizational interventions have an indirect effect on reducing depression by preventing workplace violence; however, there was no direct effect on reducing the depression of the workers. These results justify the need to invest in strengthening workplace protection systems for the interpersonal service workers.